2019
DOI: 10.4103/jpbs.jpbs_257_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of wound healing potential of manuka and acacia honey in diabetic and nondiabetic rats

Abstract: A BSTRACT Background: Manuka honey has attracted the attention of the scientific community for its antimicrobial and antioxidant properties. The active compounds of manuka honey to which its myeloperoxidase activity inhibition is owed are methyl syringate (MSYR) and leptosin (a novel glycoside of MSYR). The non-peroxide antibacterial activity is attributed to glyoxal, 3-deoxyglucosulose, and methylglyoxal. These properties make it an inexpensive and effective topical tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In a comparative study on topical application of MH and acacia honey in diabetic and normal rats, it was reported that MH achieved up to 80% wound contraction after nine days of treatment. In the MH-treated group, complete epithelialization was evident two days earlier than usual epithelialization [ 61 ].…”
Section: Mgh and Its Wound Healing Effectsmentioning
confidence: 99%
“…In a comparative study on topical application of MH and acacia honey in diabetic and normal rats, it was reported that MH achieved up to 80% wound contraction after nine days of treatment. In the MH-treated group, complete epithelialization was evident two days earlier than usual epithelialization [ 61 ].…”
Section: Mgh and Its Wound Healing Effectsmentioning
confidence: 99%
“…It was found that honey is effective bactericidal agent at wide range against both organisms 18 . Topical application of manuka honey was found to be effective and achieved ≥ 80% wound contraction in both the nondiabetic and diabetic group 19 .…”
Section: Introductionmentioning
confidence: 95%
“…Honey was found to be highly effective on the tested organisms of MRSA isolates with MIC and MBC ranging from 9.38-37.5% v/v 22 . Croatian honey, prominently honeydew honey, has been reported for its the very effective antibacterial activity and its potential to become an important additive to therapeutic techniques available to a medical practitioner against resistant pathogens 23 . Honey film has a greater effectiveness to accelerate the healing of burns and incision wounds when compared to the negative control 24 .…”
Section: Introductionmentioning
confidence: 99%
“…93 In another study, researchers compared the healing effects of topical application of manuka and acacia honey in streptozotocin-induced diabetic and nondiabetic male Wistar rats. 94 Rats were treated with an alginate gel that served as a control treatment, with manuka honey, with acacia honey, or with silver sulfadiazine cream for 21 days. Topical application of manuka honey was associated with higher wound contraction percentage and faster complete epithelialization of the wounds in both the diabetic and nondiabetic groups of animals, while this was not the case for wounds treated with acacia honey.…”
Section: Wound Healing Effects In Diabetic Animal Modelsmentioning
confidence: 99%
“…Topical application of manuka honey was associated with higher wound contraction percentage and faster complete epithelialization of the wounds in both the diabetic and nondiabetic groups of animals, while this was not the case for wounds treated with acacia honey. 94 Malkoç et al 95 evaluated the anti-inflammatory, antioxidant, and wound-healing effects of topical application of mad honey in streptozotocin-induced diabetic male Wistar albino rats. Rats received once daily topically on the wound saline solution, terramycin, or mad honey for 19 days.…”
Section: Wound Healing Effects In Diabetic Animal Modelsmentioning
confidence: 99%